Pyrrolizidine Alkaloids in Some Algerian’s Honeys - Draiaia, R; Borin, A; Martinello, M; Gallina, A; Mutinelli, F; Chefrour, A (My University, 2019)
In this research, some Algerian honey samples were collected from various geographical and botanical origins, and analyzed by LC/MS method for determination of pyrrolyzidine alkaloids. The study of 46 samples revealed the presence of PA in the honeys tested and that some contained high concentrations of this substance. 74% contained PAs with a total PAs’ concentration ranging from 1 to 748 μg/kg of PApositive samples. This study demonstrated that Algerian honeys may contain high amounts of PAs exceeding the current recommendations. Massive intoxication during honey consumption seemed unlikely. However, long-term consumption of large quantities of highly contaminated honey could lead to poisoning specially in possible additional exposure of consumer to PAs from other sources like medicinal plants, which is recognized as a potential threat to human health. For that reason, beekeepers have been advised to carry out more rigorous quality control tests to the evaluation of PAs in honeys